MATERNAL HEALTH AND INSTITUTIONAL DELIVERY AMONG TRIBAL WOMEN IN ODISHA: ANALYZING SOCIO- CULTURAL BARRIERS AND POLICY INTERVENTIONS - Dash, Sandhya Rani; Sagarika, Sipra (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the critical public health challenge of maternal morbidity and access to institutional delivery for tribal women in Odisha, India. It identifies a complex interplay of structural, socio-economic, and cultural barriers—including geographical isolation, poverty, low literacy, and strong cultural beliefs—that severely limit healthcare access. Utilizing a mixed-methods approach across four tribal-dominated districts, the research reveals a paradoxical finding: while government schemes like Janani Suraksha Yojana (JSY) and Janani Shishu Suraksha Karyakram (JSSK) have successfully increased institutional delivery rates to 76.5% among Particularly Vulnerable Tribal Groups (PVTGs), a significant disparity in maternal mortality ratios (MMR) persists between tribal and non-tribal populations. This gap is attributed to a critical awareness deficit, with 65% of tribal women unaware of maternal health schemes, coupled with inadequate infrastructure, nutritional deficiencies, and persistent home deliveries (23.5%). The discussion concludes that merely promoting institutional delivery is insufficient. Achieving equitable maternal health outcomes requires culturally sensitive, multi-faceted interventions that address deep-rooted structural barriers, enhance community-specific awareness, and improve the quality and accessibility of healthcare services in remote tribal regions.